Sharing Death - Christensen, Dorthe Refslund; Sandvik, Kjetil; Klastrup, Lisbeth; Gotved, Stine; Pennington, Natalie (AoIR Selected Papers of Internet Research, 2013)
For some years, uttering the view that modern Westerners are afraid of death seem to have been considered stating the obvious. However, in the light of web 2.0, social media and new possibilities of online networking, this self-evident statement can – and must - be seriously challenged. In fact, one might argue, that humans share death as never before. The papers in this panel all set out to explore how digital practices of Sharing Death – however different – can be considered social technologies that produces, negotiate and develop social relations, belonging and coherence.For decades, philosopher Martin Heidegger, have been the most quoted Western thinker on death, considering death to be basically non-relational (Heidegger 1962: 358) and final – an event that radically ends ones Dasein (Being-there). However, in a new book, Taming Time – Timing Death. Social Technologies and Ritual (2013), Willerslev, Christensen and Meinert breaks with Heidegger (1962, and Derrida 2003 and Badiou 2005) by turning towards the French philosopher Claude Romano (2009) who suggests that death in itself is nothing and that this nothing IS death and, furthermore, that the death of others cannot be experienced by me since it is he or she and not I that dies. So what am I experiencing when faced with a cataclysm of death? According to Romano, I am faced with my own death in the sense that the parts of me that existed only in the relation with the deceased are now dead since it was the interactions with the deceased that made relevant these parts of me. Willerslev, Refslund Christensen and Meinert suggest:death is inherently social in the sense that it pre-exists us, we handle it socially and we experience death through the death of others. It is always already in place, waiting to assign us a place within its sphere and to/thereby redefine our social relations. It is often not understood as finitude per se, but as a transitory realm that transports us into another state of communal existence (Willerslev, Refslund Christensen & Meinert 2013: 5)The papers in this panel reflects the claim that death is inherently social and that there exists intricate relations between ’me’ and ’others’, ’before’ and ’after’ death, and between different realms of existences in the analyzed practices. The short papers reflect communication from the living to the dead and vice versa. It documents peer to peer support initiatives as well as more public and community building practices. While Pennington focuses on interactions of the bereaved to a person dead from suicide and thereby on the way this kind of death is represented by the bereaved Klastrup offers insights to the tendency to the R.I.P’ing pages where people mourn the deaths of celebrities or victims of publicly acknowledged deaths. Christensen & Sandvik puts attention to the sharing of deaths of stillborns and infants at a Danish online memorial site while Gotved focuses on the new trend of QR codes on gravestones through which pre-produced info on the dead can be obtained.Through the papers on this variety of digital practices, the panel establishes how death is social and relational as never before. We use the death of others, both to commemorate them and, not the least, to reflect on who we are, now that they are not in the world anymore.References:Badiou, A. 2005. Being and Event, New York: Continuum International Publishing Group Ltd.Derrida, J. 2003. A Certain Impossible Possibility of Saying the Event. Critical Inquiry, 33, pp. 441–61.Heidegger, M. 1962. Being and Time. New York: Harper & RowRomano, C. 2009. Event and World, New York: Fordham University PressWillerslev, R., Christensen, D. R. & Meinert. L. 2013. Introduction. In: Christensen, D. R. & Willerslev, R. (eds.). Taming Time, Timing Death. Social Technologies and Ritual, Surrey: Ashgate, pp. 1-16